COMPARATIVE STUDIES WITH DIFFERENT CYCLODEXTRIN DERIVATIVES IN IMPROVING THE SOLUBILITY AND DISSOLUTION OF SAQUINAVIR - Sogali, Bharani S; Bn, Vikram; Murthy Kv, Ramana (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The present study was aimed to perform comparative studies with different cyclodextrin (CD) derivatives and to study the effect of different methods of preparation in improving the solubility and dissolution of saquinavir (SQV). Methods: Phase solubility studies were performed with beta CD (Î²CD), hydroxypropyl Î²CD, randomly methylated Î²CD, and sulfobutyl ether Î²CD (SBE7Î²CD). Complexes were prepared using physical mixture, coevaporation, kneading, spray drying, and freeze-drying techniques. For complexes prepared by spray drying, process parameters were optimized based on percentage yield. The prepared complexes were characterized using Fourier-transform infrared spectroscopy, differential scanning calorimetry, X-ray diffraction studies, nuclear magnetic resonance spectroscopy, and scanning electron microscopy. In vitro drug release study was conducted in phosphate buffer pH 6.8 and mean dissolution time (MDT) was calculated for all freeze-dried complexes. Results: Phase solubility studies showed a linear relationship with an increase in CD concentration and phase diagrams were of AL type. Highest stability constant was observed with SQV-SBE7Î²CD (8281.28/M). All characterization studies proved complexation. Among four CD derivatives, SQV complexed with SBE7Î²CD by freeze-drying showed maximum drug release and low MDT of 20.67. Conclusion: Among different CDs, SBE7Î²CD proved as ideal CD derivative, and among different methods of preparations, freeze-drying method was found to be useful in improving the solubility and dissolution of SQV.